(untitled) (The Lumbini Journal of Business and Economics, 2022)
The objective of the study is to analyze the factors affecting employee job satisfaction in restaurants in Butwal, Nepal. The independent variables under study are: working conditions, remuneration, employees’ relationship with supervisors, and co-worker relations, while the dependent variable is employees’ job satisfaction. The structured questionnaire survey was conducted by taking a sample of 92 respondents from the grade ‘A’ level restaurant of Butwal area. The descriptive research design using correlation and regression was used to analyze the data. Primary data was collected from sampled staff of Restaurant industry of Butwal. The summarized data is presented using percentages and presented using tables and pie charts. Research ethics were observed before, during and after carrying out the research. Study results indicate that two factors remuneration plan and relationship with co-workers had a significant relationship with dependent variable. The findings also indicate that factors attributes to working conditions and relationship with supervisors were the most statistically significant independently with employee’ job satisfaction.